Perbedaan Waktu Shalat Jum’at Di Masjid Distrik Jayapura Selatan: Sebuah Tinjauan Fiqih Dan Ilmu Falak: The Difference in Friday Prayer Times at Mosques in South Jayapura District: A Jurisprudential and Astronomical Review - Farhan, Muhammad; Faradiba, Nur Shinta; Rahman, Hendra Yulia (ISTIDLAL, 2025)
This study was motivated by the phenomenon of differences in the timing of Friday prayers in a number of mosques in South Jayapura District, reflecting variations in the application of Sharia law due to differences ininterpretation of the timing of prayers. The study aims to identify the factors causing these differences and analyze them from Fiqih and Ilmu Falak review. Using a qualitative method with a normative-empirical approach and descriptive-analysis research type, data was collected through in-depth interviews with religious leaders and mosque administrators, as well as direct observations at nine mosques. The results of the study indicate that differences in the timing of Friday prayers are influenced by internal mosque policies, the discipline of staff, the readiness of congregants, differences in the use of clocks or timers, and weak coordination between mosques. In fiqh, Friday prayers are valid as long as they are performed within the Zuhr time frame (after zawal until before Asr), while astronomy precisely determines the time through calculation, which is 11:52 WIT. In conclusion, these differences reflect the dynamics between the flexibility of Islamic law and astronomical precision, which require synergy to achieve uniformity in the timing of Friday prayers in the region.